Albanian-style laïcité: A Model for a Multi-religious European Home?. Issue 1 (2nd January 2017) - Elbasani, Arolda; Puto, Artan
Abstract: As a Muslim-majority and multi-denominational polity, Albania has historically searched for suitable institutional solutions to reconcile Islam with a pluralist society, a unitary nation and often fragile European statehood. The post-Communist solutions for the management of this frail plurality are commonly framed within a local tradition of laïcité (Alb. shtet laik ), which adapts the French model of separation between state and religion to particular Albanian goals and compromises. The analysis in this article explores the continuities and changes that mark the Albanian brand of laïcité, with a focus on specific solutions for managing the Islamic majority. The analysis suggests that home-grown interpretations of laïcité capitalize on historical precedents—or traditional solutions—that proved successful in accommodating Islam, religious plurality and European statehood during the founding of the independent Albanian state. Similarly to the past, post-Communist choices insist on safeguarding a local traditional version of Islam, which provides backing for the country's consensual political goals of national unity and European anchorage.